Comment on Ribstein's Incorporating the Hendricksons - Robert C. Ellickson (Washington University Journal of Law & Policy, 2011)
This Essay discusses Larry Ribstein's essay "Incorporating the Hendricksons," which focuses on the differences between domestic and business relations. The author here argues that the convergence of such relations is improbable. He adds that Ribstein did not mention the possibility that a business marriage partner will transfer assets to a marital corporation. The author also addresses Kraakman and Hansmann's thesis on the purpose of asset partition.
Keywords: Domestic relations; Corporations; Liberty of contract; Cost effectiveness; Business associations; Partnerships